2015
DOI: 10.1017/s1368980015002281
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in prevalence of overweight and obesity, and in extent of overweight index, in children and adolescents (3–18 years) from Kraków, Poland in 1983, 2000 and 2010

Abstract: Objective: The increasing prevalence of overweight and obesity among children is now an important health problem. This fact, however, does not reflect the scale of the problem. The aim of the present study was to find how much the BMI threshold was exceeded in a population from Kraków. Design: The study was based on three cross-sectional surveys conducted in 1983, 2000 and 2010. The prevalence of overweight and obesity was estimated based on the International Obesity Task Force cut-off points. In addition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
2
11
1
1
Order By: Relevance
“…However, the finding was not homogenous. The prevalence of overweight or obesity tended to be higher in girls than boys in some LMICs while a reverse pattern was found in other countries, consistent with findings in previous studies . Sex differences in overweight may reflect cultural factors and differences in physical activity levels .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the finding was not homogenous. The prevalence of overweight or obesity tended to be higher in girls than boys in some LMICs while a reverse pattern was found in other countries, consistent with findings in previous studies . Sex differences in overweight may reflect cultural factors and differences in physical activity levels .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of excess weight did not differ substantially between ages of 12–13 and 14–15 years in our study, although previous studies found higher prevalence of overweight in early versus late adolescence . This may be due to the narrow age range in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…This phenomenon is similar to some European countries [27,28], but it was not observed in Jordan [29] or Hungary [30]. The higher prevalence observed in boys might be related to China’s traditional culture, different views of what body shape is most aesthetically pleasing for boys versus girls, and different requirements for their stature [31].…”
Section: Discussionsupporting
confidence: 71%
“…Kowal i wsp. [14], badając dzieci w wieku 3-18 lat z terenu Krakowa w latach 1983, 2000 i 2010, zaobserwowali, że zwiększenie częstości występo-wania nadwagi i otyłości dotyczyło przede wszystkim chłopców, u dziewcząt częstość pozostała na podobnym poziomie. Meigen i wsp.…”
Section: Materiał I Metodyunclassified